The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/chem.202003153
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostibination of Alkynes: A Radical Mechanism**

Abstract: The addition of Sb-H bonds to alkynes was reported recently as a new hydroelementation reaction that exclusively yields anti-Markovnikov Z-olefins from terminal acetylenes. We examine four possible mechanisms that are consistent with the observed stereochemical and regiochemical outcomes. A comprehensive analysis of solvent, substituent, isotope, additive, and temperature effects on hydrostibination reaction rates definitively refutes three ionic mechanisms involving closed-shell charged intermediates. Instead… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
1
4
0
Order By: Relevance
“…25 The mechanism for hydrobismuthation was examined with DFT. Similarly to the results of Chitnis and co-workers for hydrostibination, 26 all closed-shell pathways leading to 2 were found to have significant energy barriers and are, therefore, unfeasible under the experimental conditions. Consequently, a radical mechanism was sought, which led to the characterization of transition states TS-1 for hydrogen transfer from 1 to phenylacetylene (Figure 4).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…25 The mechanism for hydrobismuthation was examined with DFT. Similarly to the results of Chitnis and co-workers for hydrostibination, 26 all closed-shell pathways leading to 2 were found to have significant energy barriers and are, therefore, unfeasible under the experimental conditions. Consequently, a radical mechanism was sought, which led to the characterization of transition states TS-1 for hydrogen transfer from 1 to phenylacetylene (Figure 4).…”
supporting
confidence: 76%
“…In contrast the mechanism for hydrostibination follows a pathway in which the stibinyl and 1-phenylvinyl radicals separate, allowing the former to add to an equivalent of phenylacetylene and undergo a second hydrogen transfer to give the anti-Markovnikov product. 26 In this context, the dissociation of INT-1 to bismuthinyl and 1-phenylvinyl radicals was calculated to be an entropy-driven process, while the transition state associated with the addition of the bismuthinyl radical to phenylacetylene was found to be energetically on par with TS-1. Thus, the recombination of bismuthinyl and 1-phenylvinyl radicals, as shown in Figure 4, represents the minimum energy pathway and agrees with the observed Markovnikov regioselectivity.…”
mentioning
confidence: 99%
“…They later comprehensively studied the mechanism of this hydrostibination and suggested that a radical mechanism is at play. 144 Finally, in the context of HP, it is important to note that all of the heavier-congener hydropnictogenations reported display near-perfect anti-Markovnikov selectivity.…”
Section: Heavier-congener Hydropnictogenationmentioning
confidence: 99%
“…More recently, Chitnis and co-workers reported a catalyst- and initiator-free hydrostibination by tuning the stibene backbone to stabilize the LUMO of the stibene (Scheme b). They later comprehensively studied the mechanism of this hydrostibination and suggested that a radical mechanism is at play . Finally, in the context of HP, it is important to note that all of the heavier-congener hydropnictogenations reported display near-perfect anti-Markovnikov selectivity.…”
Section: Heavier-congener Hydropnictogenationmentioning
confidence: 99%
“…We recently noted that these ligands also have the appropriate steric profile to stabilize very fragile bonds and demonstrated this application by successfully isolating reactive antimony hydrides as well as the first examples of Sb–Bi σ-bonds (Figure d,e). In the latter case, our preliminary calculations suggested that the metal–metal bond energies for some derivatives were boosted by a remarkable 60% due to London dispersion. As a consequence, Sb–Bi σ-bonds that rapidly decompose at 298 K when supported by small methyl groups were stable for several days at 373 K when the 1,8-bis­(silylamido) naphthalene ligand was used.…”
Section: Introductionmentioning
confidence: 99%